Basic principles of population oncological screening in modern radio-ecological situation: routine screening of breast cancer to personalized screening - Kostetskaya, Tatyana V.; Batyan, Anatoly N.; Labai, Maryna V. (Journal of the Belarusian State University. Ecology, 2019)
The article presents a review of the literature on the problems and prospects of breast cancer screening. The effectiveness of mammography as a screening method in reducing mortality from breast cancer is reflected, and the models and parameters of screening are indicated. The ideology of screening is based on the consideration that routine clinical examination and self-examination usually do not detect asymptomatic and early forms of cancer. Therefore, it is necessary to use such instrumental diagnostic tools that would reveal manifestations of significantly earlier forms of tumors. In the early diagnosis of breast cancer, the role of secondary prophylaxis is currently high, preventive detection of breast tumors. In the practice of health care in the countries of Western Europe and America, breast cancer screening has been conducted for several decades, which has reduced mortality from this disease in these states by 25–30 %.